Geotech acquires special effect pigments firm Paillettes et Pigments. Issue 9 (September 2016) - Unknown
Abstract : Dutch pigments producer Geotech International BV is expanding its presence in the special effect pigments market with the acquisition of French supplier Paillettes et Pigments Sarl (PEP). PEP's pearlescent pigments and glitter products serve the cosmetics, plastics and coatings industries and are used particularly in colour cosmetics, polymer masterbatches and decorative coatings. The company has been active in the European market for more than two decades, with a focus on France.